Perancangan Sistem Iot Untuk Deteksi Dan Mitigasi Kondensasi Pada Panel Sdp Melalui Pemantauan Kelembapan Dan Suhu Permukaan - Dalanta Riski Permana Tarigan; Aditya Chandra Hermawan (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Condensation inside Sub Distribution Panels (SDPs) is one of the major causes of reduced electrical distribution system reliability, leading to corrosion, insulation degradation, and short circuits. This study proposes an Internet of Things (IoT)-based system for detecting and mitigating condensation risk by monitoring internal relative humidity (RH_in) and panel surface temperature (T_surface). The system employs an SHT31 sensor and a DS18B20 sensor for data acquisition, an ESP32 microcontroller as the main controller, and a Mamdani fuzzy logic algorithm to determine the operating level of a PTC heater. A blower is controlled using an interlocking strategy to ensure uniform heat distribution inside the panel. Sensor readings and actuator status are transmitted to an IoT platform for real-time monitoring and historical data logging. System evaluation includes sensor accuracy testing, fuzzy logic validation, actuator performance testing, and integrated system testing. The expected results demonstrate that the proposed system can detect potential condensation conditions at an early stage, provide adaptive control responses, and improve the reliability  and  operational  safety  of  SDP  panels  through  effective  condensation  mitigation.